Pengaruh Sikap Wajib Pajak, Pengetahuan Perpajakan Dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Kasus Pada Pelaku Ekonomi Kreatif Sub Sektor Blended Fashion Dan Kuliner Di Kota Sumenep) - Laely Anjar Wati; Jeni Susyanti; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe study aims to analyze the influence of taxpayer attitudes, tax knowledge and quality of service on the compliance of private taxpayers on creative economists of the blended fashion and culinary sub-sector in Sumenep City. The sample used in the study used purposive sampling techniques so that the number of samples obtained was as many as 40 respondents who met the criteria. The analytical tool used in this study is multiple linear regression analysis. The results of this study showed that taxpayer attitudes, tax knowledge and service quality simultaneously have a significant influence on the compliance of private taxpayers on the creative economy of the blended fashion and culinary sub-sector in Sumenep City. Variables in taxpayer attitudes have a significant and positive effect on the compliance of private taxpayers in the creative economy of the blended fashion and culinary sub-sector in Sumenep City. The variables of tax knowledge and service quality are not in line with taxpayer compliance with the economic actors of the blended fashion and culinary sub-sector in Sumenep City. Keywords : Creative Economy Sub-Sector Blended Fashion And Culinary In Sumenep City, Taxpayer Attitude, Tax Knowledge, Quality of Service, Taxpayer Compliance